Safety, immunogenicity, and lot-to-lot consistency of a quadrivalent inactivated influenza vaccine in children, adolescents, and adults: A randomized, controlled, phase III trial. Issue 21 (15th May 2015) - Cadorna-Carlos, Josefina B.; Nolan, Terry; Borja-Tabora, Charissa Fay; Santos, Jaime; Montalban, M. Cecilia; de Looze, Ferdinandus J.; Eizenberg, Peter; Hall, Stephen; Dupuy, Martin; Hutagalung, Yanee; Pépin, Stéphanie; Saville, Melanie
Highlights Safety profiles in adults and children/adolescents were similar for IIV4 and IIV3. Antibody responses to IIV4 and IIV3 were similar for corresponding strains. IIV4 produced comparable antibody responses in children/adolescents and adults. The immunogenicity of IIV4 in adults complied with EMA criteria. Three lots of IIV4 had equivalent safety and immunogenicity profiles.